ANALISIS KUALITAS WEBSITE PT.POS INDONESIA MENGUNAKAN PENDEKATAN WEBQUAL 4.0 MENURUT PERSEPSI ONLINE SELLER - Apit Priatna; Arif Maulana Yusuf; Ulia Rahma; Vera Wati; Muhammad Edi Iswanto; Joko Irawan (LPPM Universitas Abdurrab, 2026)
The rapid development of information technology encourages companies to utilize websites as a medium for providing information and services to users effectively and efficiently. PT. Pos Indonesia, as a courier and logistics service company, utilizes its website to provide various digital services such as tariff information, service coverage areas, and shipment tracking. However, several issues related to website quality have been identified based on user experiences. This study aims to analyze the quality of the PT. Pos Indonesia website based on user perceptions, particularly among online sellers in Karawang Regency. The method used in this study is Webqual 4.0, which measures website quality based on three main dimensions: usability, information quality, and service interaction quality. This research employs a quantitative approach with data collection conducted through questionnaires distributed to 100 respondents who are users of the PT. Pos Indonesia website. The data were analyzed using descriptive statistics and the Importance Performance Analysis (IPA) method to determine the level of conformity between the importance and performance of website services. The results show that the average importance score is 4.39, while the average performance score is 3.03, resulting in a gap value of -1.36. The negative gap value indicates that the quality of the PT. Pos Indonesia website has not fully met user expectations. Therefore, improvements are required in several website service attributes in order to enhance digital service quality and user satisfaction.